Arterial stiffness can predict cardiorespiratory fitness in type 2 diabetic patients? - Monteiro, Clara Italiano; Simões, Rodrigo Polaquini; Heubel, Alessandro Domingues; da Silva, Claudio Donisete; Ricci, Paula Angélica; Petronilho, Ariane; Borghi-Silva, Audrey; Mendes, Renata Gonçalves (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Arterial stiffness (AS) has been associated with reduced cardiorespiratory fitness (CRF). The aim of this study was to verify if there is a relationship between augmentations index (AIx), as an index for AS assessment, and CRF in individuals with type 2 Diabetes Mellitus (T2DM). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Observational cross-sectional study including 32 individuals diagnosed with T2DM who performed two evaluations: 1. Arterial stiffness assessment using SphygmoCor and 2. CRF throughout a cardiopulmonary exercise test on a treadmill ergometer. Oxycon Mobile® device was used to obtain oxygen uptake consumption at peak (V˙O2peak); oxygen uptake efficiency slope (OUES) determined by linear regression in reason of the logarithmic transformation of the ventilation and V˙O2 obtained every minute of exercise test. Statistical analysis comprised Pearson’s Correlation and linear regression analysis performed in SigmaPlot. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. There was a significant correlation between AS and CRF: AIx and OUES; AIx@75 and; OUES. In linear regression, AIx was determinant for V˙O2peak and OUES – AIx and; AIx@75 and V˙O2peak. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. AS was associated with CRF in individuals with T2DM. These results contribute to the body of evidence linking arterial functional properties to CRF and suggests greater attention for this important index.